Strategi Sekolah dalam Penguatan Nilai-Nilai Religius pada Masa Pandemi Covid-19 di SMA Al-Islam Krian - Nindy Puspitasari; I Made Suwanda (Kajian Moral dan Kewarganegaraan, 2023)
Religious values ​​are very important for students as the next generation of the nation as a sign of good behavior in accordance with religious law in facing the challenges of global life. This study aims to describe school strategies and obstacles in strengthening the religious values ​​of students during the Covid-19 pandemic at Al-Islam Krian High School. This research method uses a qualitative approach with a descriptive design. Data obtained through observation, interviews, and documentation. The informants of this research were the Principal, PAI Teacher, PPKn Teacher, and BK Teacher who were determined based on purposive sampling technique. The results showed that the school's strategy in strengthening the religious values ​​of students was carried out by habituation of order, habituation of religious activities, extracurricular activities, giving religious knowledge and good behavior, and providing real examples or examples. The obstacles experienced by schools are the neglect of students' parents, the uncontrolled use of students' social media by the school, and the nature of the students themselves. This study was analyzed using Ivan Pavlov's theory of behaviorism, namely the habituation of activities carried out repeatedly and accompanied by reinforcement by the school will be able to produce the behavior of students who have religious values ​​in relation to God and fellow human beings. Keywords: strategy, school, religious values.